The Crisis in Local Newspapers and Organizational Wrongdoing: The Role of Community Social Connectedness - Choi, Tony Jaehyun; Valente, Mike (Organization Science, 2023)
Drawing on institutional anomie theory, we examine how the crisis in local newspapers has induced organizational wrongdoings in local communities. We argue that, because local newspapers are the primary source of accountability journalism in local communities, their decline leads to an anomic state that increases the scale of organizational wrongdoing. We also investigate whether institutional complementarity helps overcome the anomic state: Due to functional similarity, community social connectedness compensates for the scarcity of local newspapers. Our analysis of U.S. metropolitan areas for the period of 2007–2015 reveals that the positive relationship between local newspaper scarcity and the scale of organizational wrongdoing is not present in all communities but does appear when a community lacks community social connectedness. We also find that this moderating role of community social connectedness is observed only for internal organizational wrongdoings that are less visible to the public than external ones.